Beyond Self-Report: Emerging Methods for Capturing Individual Differences in Decision-Making Process - Connors, Brenda L.; Rende, Richard; Colton, Timothy J. (Frontiers in Psychology, 2016)
People vary in the way in which they approach decision making, which impacts real-world behavior. There has been a surge of interest in moving beyond reliance on self-report measures to capture such individual differences. Particular emphasis has been placed on devising and applying a range of methodologies that include experimental, neuroscience, and observational paradigms. This paper provides a selective review of recent studies that illustrate the methods and yield of these approaches in terms of generating a deeper understanding of decision-making style and the notable differences that can be found across individuals.